2021
DOI: 10.1159/000516357
|View full text |Cite
|
Sign up to set email alerts
|

3D Breast Volume Estimation

Abstract: <b><i>Introduction:</i></b> Breast volume estimation is considered crucial for breast cancer surgery planning. A single, easy, and reproducible method to estimate breast volume is not available. This study aims to evaluate, in patients proposed for mastectomy, the accuracy of the calculation of breast volume from a low-cost 3D surface scan (Microsoft Kinect) compared to the breast MRI and water displacement technique. <b><i>Material and Methods:</i></b> Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…As a result, volume assessments rely on computer-generated models of the posterior breast borders, rendering them estimations rather than exact measurements. Nonetheless, it is worth noting that multiple authors have demonstrated a strong linear correlation between 3D surface scans and various methods of measuring breast volume, such as MRI-measured breast volume [24,25], mastectomy surgical specimens [25], and even water displacement [26].…”
Section: Limitationsmentioning
confidence: 99%
“…As a result, volume assessments rely on computer-generated models of the posterior breast borders, rendering them estimations rather than exact measurements. Nonetheless, it is worth noting that multiple authors have demonstrated a strong linear correlation between 3D surface scans and various methods of measuring breast volume, such as MRI-measured breast volume [24,25], mastectomy surgical specimens [25], and even water displacement [26].…”
Section: Limitationsmentioning
confidence: 99%
“…At present, the lack of a simple and replicable method to calculate it limits its applicability in practice. Among the various techniques available, manual anthropometric measurements, the Archimedes method (based on water displacement), the Grossman–Roudner device (which uses conical discs inside which the breast is placed), mammography, CT, MRI and 3D surface imaging can be highlighted [ 24 , 25 ].…”
Section: Preoperative Applicationsmentioning
confidence: 99%
“…5 However, recent studies have described the value of 3D imaging in the assessment of breast volume. 1,[6][7][8][9][10][11] The Vectra H2 (Canfield Scientific, Parsippany, N.J.; Fig. 1) is an easy-to-use handheld 3D camera that can construct 3D data for both breasts with a personal computer (PC) application after taking images in three directions.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, recent studies have described the value of 3D imaging in the assessment of breast volume. 1,6–11…”
Section: Introductionmentioning
confidence: 99%